Perancangan Strategi Marketing UMKM Dizert Dessert Di PT. Kawakibi Digital Branding (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2024)
Marketing is an activity where business actors offer their products to consumers so that they can accept the product with all the ideas and ideas so that the product can be sought after by consumers. Of the many UMKM products, kawakibi offers its services to help UMKM players develop their brand image and increase product sales through social media. PT. Kawakibi Digital Branding is a company that has a main focus on the branding sector. With an innovative and creative approach, Kawakibi strives to help companies and brand logos build strong relationships with potential consumers and achieve long-term success in this competitive industrial world. The results of this research can be used as a reference for designers and readers in utilizing marketing strategies.